1994
DOI: 10.1051/jp4:1994102
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity studies on solid polymer electrolytes

Abstract: This thematic lecture addresses electrochemical conductivity techniques for the study of solid polymer electrolytes. Types of conductivity are discussed first, followed by an outline of the features, applicability, and validity of DC and AC conductivity measurements. Techniques for the identification of the individual species responsible for conduction are then briefly reviewed. RésuméCette étude aborde des méthodes de mesure de conductivité électrique des électrolytes polymères solides. On considère d' abord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The value of C in a typical blocking-electrode conductivity cell is largely controlled by the geometric cellcapacitance, and hence by the electrode configuration. 37 Consistent with this description, C remained in the nF regime, essentially independent of the applied temperature variations.…”
Section: Impedance Spectroscopic Measurement Of Ionic Conductivitysupporting
confidence: 63%
“…The value of C in a typical blocking-electrode conductivity cell is largely controlled by the geometric cellcapacitance, and hence by the electrode configuration. 37 Consistent with this description, C remained in the nF regime, essentially independent of the applied temperature variations.…”
Section: Impedance Spectroscopic Measurement Of Ionic Conductivitysupporting
confidence: 63%
“…They: (i) favor the formation of the salt complex, leaving a film depleted in free polymer; (ii) hinder complete salt dissociation; (iii) facilitate the formation of ionic multiplets, such as triplets (X-M+ X-, M+ X-M+) and quartets (M+ X-M+ X-), which are less mobile than free ions, which decreases their effective concentration; (iv) diminish the number of vacancies available for ionic transport. All of these effects contribute together to the low conductivities observed at higher salt concentration [17]. Figure 3(b) illustrates the temperature dependence of the conductive ity of the sample B.…”
Section: Resultsmentioning
confidence: 96%
“…PEs as part of an innovative class of materials are widely applied in devices [26]. Many investigational studies have confirmed the importance of adding low molecular weight plasticizers into the PEs for enhancing ion migration [27].…”
Section: Impedance Studymentioning
confidence: 99%